CHARACTERIZATION OF 0.58 kb DNA STILBENE SYNTHASE ENCODING GENE FRAGMENT FROM MELINJO PLANT (Gnetum gnemon) - Tri Joko Raharjo; Rosyida Azis Rizki; Stalis Norma Ethica; Elly Rustanti; L. Hartanto Nugroho (Universitas Gadjah Mada, 2011)
Resveratrol is a potent anticancer agent resulted as the main product of enzymatic reaction between common precursor in plants and Stilbene Synthase enzyme, which is expressed by sts gene. Characterization of internal fragment of Stilbene Synthase (STS) encoding gene from melinjo plant (Gnetum gnemon L.) has been carried out as part of a larger work to obtain a full length of Stilbene Synthase encoding gene of the plant. RT-PCR (Reverse Transcriptase Polymerase Chain Reaction) was performed using two degenerated primers to amplify the gene fragment. Ten published STS conserved amino acid sequences from various plant species from genebank were utilized to construct a pair of GGF2 (5' GTTCCACCTGCGAAGCAGCC 3') and GGR2 (5' CTGGATCGCACATCC TGGTG 3') primers. Both designed primers were predicted to be in the position of 334-354 and 897-916 kb of the gene respectively. Total RNA isolated from melinjo leaves was used as template for the RT-PCR amplification process using two-step technique. A collection of 0.58 DNA fragments was generated from RT-PCR amplification and met the expected results. The obtained DNA fragments were subsequently isolated, refined and sequenced. A nucleotide sequence analysis was accomplished by comparing it to the existed sts genes available in genebank. Homology analysis of the DNA fragments with Arachis hypogaea L00952 sts gene showed high similarity level. Taken together, the results are evidence that the amplified fragment obtained in this study is part of melinjo sts gene